Gallium-doped zinc oxide nanorods for photocatalytic performance under solar irradiation / Sulaiman S.A. Alghafri - Sulaiman , S.A. Alghafri (2022)
In this thesis, a rapid microwave-assisted method has been used to synthesize pristine and gallium (Ga) doped ZnO nanorods on the glass substrates. With different percentages of the concentration of the gallium nitrate compound in the seeding and growth solutions, the samples were labeled to 0.5%, 1%, 3% and 5% Ga-doped ZnO nanorods. These samples were used to degrade artificial water pollutants by adding methylene blue dye in water and to track the percentage of analysis for each sample. Prepared samples were characterized by X-Ray Diffraction (XRD), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray (EDX), Atomic Force Microscopy (AFM), UV-Vis spectroscopy, Photoluminescence (Shtepliuk) spectroscopy, Fourier Transform Infra-red (FTIR) spectroscopy, X-ray Photoelectron Spectroscopy (XPS) and methylene blue degradation photo-catalyst efficiency analysis. The degradation of methylene blue in the presence of a prepared sample has been followed systematically. The results showed that the diameter and length of the nanorods significantly change with Ga doping from 0% to 5% from 63.2 ± 0.2 to 85.2 ± 0.2 nm diameter and from 0.64 ± 0.01 to 2.08 ± 0.02 μm length. Comparably, the crystal orientation and surface oxidation states from mean crystallite grain size (D) and the FWHM values at the peak position are also Ga content dependent. The existence of Ga-O bonds in the ZnO lattice is evidenced by XRD, which confirms the effective Ga-doping of ZnO NRs. The 1% Ga doping sample showed significant enhancement in visible light absorption, effective change carrier separation, and rapid degradation rate (60 min) compared to the pristine sample.